نشأة علم التاريخ في الحضارة العربية والإسلامية وأثر القصص القرآني في هذه النشأة - عطية، عطية محمد; حسين، جمال طه (جامعة عين شمس - كلية الآداب, 2015)
The goodness of God to human beings that sent them prophets and apostles, Vhmlhm Secretariat publication of his religion and communicate his messages and supported them holy books and miracles. Per Messenger was with his people line positions us some Quran. The Tnaht us news of the past two tribes by the Qur'an and the Hadith. And carried the stories of the prophets are many lessons, lessons, prompting the majority of Arabs and Muslims historians members private writings dealt with the history of the evolution of human civilization, which has encouraged the emergence of the science of history in the Arab-Islamic civilization. For this purpose, this study came in four chapters: the first included them views of scientists in the meaning of the word history, and in the second development of the science of history, as the third chapter genesis of the historical school, and in the fourth the impact of Quranic stories on this development, and the study concluded several results.
إن من نعم الله على البشر أن بعث إليهم الأنبياء والرسل، فحملهم أمانة نشر دينه وتبليغ رسالاته وأيدهم بالكتب السماوية وبالمعجزات. فكان لكل رسول مع قومه مواقف سطر لنا القرآن بعضها. وقد تناهت إلينا أخبار الماضين من الأقوام عن طريق القرآن والحديث النبوي. وحملت قصص الأنبياء العديد من العبر والدروس، مما دفع غالبية المؤرخين العرب والمسلمين إفرادها بمؤلفات خاصة تناولت تاريخ تطور الحضارة البشرية، مما شجع على نشأة علم التاريخ في الحضارة العربية الإسلامية. لأجل هذا، جاءت هذه الدراسة في أربعة فصول: شمل الأول منها آراء العلماء في مدلول كلمة التاريخ، وفي الثاني تطور علم التاريخ، كما تناول الفصل الثالث نشأة المدارس التاريخية، وفي الرابع أثر القصص القرآني على هذا التطور، وانتهت الدراسة إلى عدة نتائج.
Keywords: الحضارة العربية -- الحضارة الإسلامية -- علم التاريخ -- علم القراءات -- القصص القرائية